The effects of n-3 fatty acids from flaxseed oil on genetic and metabolic profiles in patients with gestational diabetes mellitus: a randomised, double-blind, placebo-controlled trial. Issue 7 (14th April 2020) - Jamilian, Mehri; Tabassi, Zohreh; Reiner, Željko; Panahandeh, Ida; Naderi, Fatemeh; Aghadavod, Esmat; Amirani, Elaheh; Taghizadeh, Mohsen; Shafabakhsh, Rana; Satari, Mahbobeh; Mansournia, Mohammad Ali; Memarzadeh, Mohammad Reza; et al.
Abstract: The present study was performed to evaluate the effects of n -3 fatty acids from flaxseed oil on genetic and metabolic profiles in patients with gestational diabetes mellitus (GDM). This randomised, double-blind, placebo-controlled clinical trial was performed in sixty women with GDM. Participants were randomly divided into two groups to intake either 2 × 1000 mg/d n -3 fatty acids from flaxseed oil containing 400 mg α -linolenic acid in each capsule ( n 30) or placebo ( n 30) for 6 weeks. n -3 Fatty acid intake up-regulated PPAR- γ ( P < 0·001) and LDL receptor ( P = 0·004) and down-regulated gene expression of IL-1 ( P = 0·002) and TNF- α ( P = 0·001) in peripheral blood mononuclear cells of subjects with GDM. In addition, n -3 fatty acid supplementation reduced fasting plasma glucose ( P = 0·001), insulin levels ( P = 0·001) and insulin resistance ( P < 0·001) and increased insulin sensitivity ( P = 0·005) when compared with the placebo. Additionally, n -3 fatty acid supplementation was associated with a decrease in TAG ( P < 0·001), VLDL-cholesterol ( P < 0·001), total cholesterol ( P = 0·01) and total cholesterol:HDL-cholesterol ratio ( P = 0·01) when compared with placebo. n -3 Fatty acid administration was also associated with a significant reduction in high-sensitivity C-reactive protein ( P = 0·006) and malondialdehyde ( P < 0·001), and an increase in total nitrite ( P < 0·001) and total glutathione levels ( P = 0·006) when compared with the placebo. n -3 Fatty acid supplementation for 6 weeks to women with GDM had beneficial effects on gene expression related to insulin, lipid and inflammation, glycaemic control, lipids, inflammatory markers and oxidative stress.